Legitimizing Empire: Racial and Gender Politics Of the War on Terrorism - Zacharias, Usha (Social justice, 2003)
Studies in the cultural politics of colonialism have shown how racial politics is almost invariably tangled with a politics of gender; in fact, one is necessary for the other. The very separation of races is based on the cultural and social policing of interracial gender and sexual boundaries, as well as interracial interactions. As feminist scholars have pointed out, war is an integral part of capitalist patriarchal culture, it silences and disempowers women, excludes them from decision-making processes, ties their rights to nationalist objectives and demands a misogynistic, masculinist culture of emotional steel from both men and women.